2023
DOI: 10.3390/ijms24109030
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Methicillin-Resistant Staphylococcus aureus with Targeted Nanoparticles

Abstract: Antimicrobial resistance (AMR) is considered one of the greatest threats to global health. Methicillin-resistant Staphylococcus aureus (MRSA) remains at the core of this threat, accounting for about 90% of S. aureus infections widespread in the community and hospital settings. In recent years, the use of nanoparticles (NPs) has emerged as a promising strategy to treat MRSA infections. NPs can act directly as antibacterial agents via antibiotic-independent activity and/or serve as drug delivery systems (DDSs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…It is responsible for endocarditis, chronic osteomyelitis, pneumonia and osteoarthritis. Among the main mechanisms of antibiotic resistance, in the case of members of this species, we note the change in the consistency of the cell wall, the presence of a greater number of efflux pumps in the external cellular structures and biofilm formation [ 48 , 49 ]. In this context, highlighting a possible sensitivity to the plant extract MOE may prove to be valuable for the development of alternative strategies to combat this pathogen both in the case of systemic and local infections.…”
Section: Resultsmentioning
confidence: 99%
“…It is responsible for endocarditis, chronic osteomyelitis, pneumonia and osteoarthritis. Among the main mechanisms of antibiotic resistance, in the case of members of this species, we note the change in the consistency of the cell wall, the presence of a greater number of efflux pumps in the external cellular structures and biofilm formation [ 48 , 49 ]. In this context, highlighting a possible sensitivity to the plant extract MOE may prove to be valuable for the development of alternative strategies to combat this pathogen both in the case of systemic and local infections.…”
Section: Resultsmentioning
confidence: 99%
“…One such strategy currently being explored is the delivery of antibiotics or antimicrobials in general via nanomedicines [ 19 , 20 , 21 ]. For example, it has been reported that Dapto encapsulated in polymeric nanoparticles demonstrated higher activity towards established Staphylococci biofilms compared to the free drug [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Additionally, Methicillin-Resistant Staphylococcus aureus (MRSA) exhibits global dissemination, associated with approximately 90 % of cases of infections acquired in both hospital and community settings. [15] Therefore, this research aims to evaluate the biological activities (antioxidant, antibacterial, and anti-biofilm formation) of geopropolis from Melipona scutellaris (uruçu bee) against S. aureus isolates with the purpose of contributing to a natural therapeutic alternative for combating infections caused by this pathogen.…”
Section: Introductionmentioning
confidence: 99%